The Evolution οf War Conflicts. The Fourth Military Revolution (RMA) & Operational Applications - Paounis, Nicholas (HAPSc Policy Briefs Series, 2020)
The phenomenon of War, historically could be characterized as multidimensional. War, that is, the confluence of military forces, over the course of the Centuries, has differed in terms of Strategic Concept, in terms of Doctrine of Operations, and in terms of technological capabilities. At the heart of the new form taken by the phenomenon of war is the possibility of mass collection and utilization of information, in combination with the technological development of weapons systems. New technologies have also attracted the doctrines of military operations. Traditional military forces, but also emerging ones, are at the forefront of new developments in the field of war.